Sunnier, denser and more productive cities - Michael Brolley; John Hartwick (Queen's University, Department of Economics, 2008)
We set out an open, monocentric city with residential structures and reflect how changes to the amenity index affects the city. On the consumption side an amenity is represented by an exogenous boost to the utility of a resident's current commodity bundle. The cities population, land rent and footprint expand and its density rises. We test for an amenity effect in local wages with household data for the US in 1990 and discover the city density is much stronger in explaining local premia than is the city population. We test for amenity effects in local house prices with the same data set.
Keywords: J61; R14; 330; Climatic amenities; Density; Wages; Stadtentwicklung; Kommunalplanung; Ballungsraum; Lebensqualität; Produktivität; Lohnniveau; USA